Neuroimaging correlates of syndromal depression following traumatic brain injury: A systematic review of the literature. (October 2022) - Richey, Lisa N.; Bryant, Barry R.; Krieg, Akshay; Bray, Michael J. C.; Esagoff, Aaron I.; Pradeep, Tejus; Jahed, Sahar; Luna, Licia P.; Trapp, Nicholas T.; Adkins, Jaxon; Jones, Melissa B.; Bledsoe, Andrew; et al.
Objective: To complete a systematic review of the literature examining neuroimaging findings unique to co-occurring syndromal depression in the setting of TBI. Methods: A PRISMA compliant literature search was conducted in PubMed (MEDLINE), PsychINFO, EMBASE, and Scopus databases for articles published prior to April of 2022. The database query yielded 4447 unique articles. These articles were narrowed based on specific inclusion criteria (e.g., clear TBI definition, clear depression construct commenting on the syndrome of major depressive disorder, conducted empirical analyses comparing neuroimaging correlates in TBI subjects with depression versus TBI subjects without depression, controlled for the time interval between TBI occurrence and acquisition of neuroimaging). Results: A final cohort of 10 articles resulted, comprising the findings from 423 civilians with brain injury, 129 of which developed post-TBI depression. Four articles studied mild TBI, three mild/moderate, one moderate/severe, and two all-comers, with nine articles focusing on single TBI and one including both single and recurrent injuries. Spatially convergent structural abnormalities in individuals with TBI and co-occurring syndromal depression were identified primarily in bilateral frontal regions, particularly in those with damage to the left frontal lobe and prefrontal cortices, as well as temporal regions including bilateral temporal lobes, the left superior temporal gyrus, and bilateral hippocampi. Various parietal regions and the nucleus accumbens were also implicated. EEG studies showed supporting evidence of functional changes in frontal regions. Conclusion: Additional inquiry with attention to TBI without depression control groups, consistent TBI definitions, previous TBI, clinically diagnosed syndromal depression, imaging timing post-injury, acute prospective design, functional neuroimaging, and well-defined neuroanatomical regions of interest is crucial to extrapolating finer discrepancies between primary and TBI-related depression.